2002
DOI: 10.1139/w02-054
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the rhizosphere-competent biocontrol strainPseudomonas fluorescensNBRI2650 in the soil and phytosphere

Abstract: Pseudomonas fluorescens NBRI2650 was isolated after screening 360 bacterial strains from the rhizosphere of chickpea (Cicer arietinum L.) grown in fungal-disease-suppressive field soil. The strain was selected because of its high rhizosphere competence and ability to inhibit the growth of Fusarium oxysporum f.sp. ciceri, Rhizoctonia bataticola, and Pythium sp. under in vitro conditions. Survival and colonization of NBRI2650 in the phytosphere of chickpea, cotton (Gossypium hirsutum L.), cucumber (Cucumis sativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The development of rhizosphere microbial communities is influenced by the plant, but in turn, microorganisms exert profound effects on plant growth. The rhizosphere of plants is therefore one of the most fascinating microbial habitats for basic and applied studies in the field of environmental microbiology, as it is shaped by the soil, the plant and the microorganisms (Nautiyal et al 2002(Nautiyal et al , 2008. Plant roots become quickly colonized by a diverse microflora of soil-borne bacteria and fungi that may have either beneficial or deleterious effects on the plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of rhizosphere microbial communities is influenced by the plant, but in turn, microorganisms exert profound effects on plant growth. The rhizosphere of plants is therefore one of the most fascinating microbial habitats for basic and applied studies in the field of environmental microbiology, as it is shaped by the soil, the plant and the microorganisms (Nautiyal et al 2002(Nautiyal et al , 2008. Plant roots become quickly colonized by a diverse microflora of soil-borne bacteria and fungi that may have either beneficial or deleterious effects on the plant.…”
Section: Introductionmentioning
confidence: 99%
“…This rhizosphere effect is primarily due to the influx of mineral nutrients to the plant roots through mass flow and diffusion, alongside the efflux and accumulation of plant root exudates. Thus, most rhizosphere bacteria and fungi are highly dependent on associations with plants that are clearly regulated by root exudates (Nautiyal et al 2002;Bais et al 2004;Bonfante and Anca 2009;Hamer and Makeschin 2009;Schroeckh et al 2009;Zubek et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Generally, the introduction of new microorganisms produces only restricted spatial and temporal effects on the soil, rhizosphere, and root microbial communities (4,29,35). Thus, the plant growth-promoting effect of such treatments may be related to microbial events occurring during the early stages of plant development.…”
mentioning
confidence: 99%
“…Molecular studies leading to determine the occurrence of ISR in beanXapf pathosystem are in progress. However, a direct effect of rhizobacteria on the pathogen at the infection site cannot be excluded since it has been reported that bacteria applied to soil or on seeds colonise rhizosphere and then may move up to the phylloplane (Nautiyal et al 2002) or to behave as either facultative or opportunistic endophytes (Hardoim et al 2008). Some characters shown by rhizobacteria under study may be the responsible of the possible direct antagonism exerted on the pathogens.…”
Section: Fagioli DI Sarconi Seed Disinfectionmentioning
confidence: 99%